Spatiotemporal Invasion Severity of Chinese Tallow (Triadica sebifera) and Invasibility of Forest Types in Southern US Forestlands. Issue 5 (22nd July 2021) - Nepal, Sunil; Moser, W Keith; Fan, Zhaofei
Abstract: Quantifying invasion severity of nonnative invasive plant species is vital for the development of appropriate mitigation and control measures. We examined more than 23, 250 Forest Inventory and Analysis (FIA) plots from the southern coastal states of the United States to develop an alternative method to classify and map the invasion severity of Chinese tallow ( Triadica sebifera ). Remeasured FIA plot-level data were used to examine the spatiotemporal changes in the presence probability and cover percentage of tallow. Four invasion severity classes were identified by using the product of presence probability and cover percentage. Chinese tallow invasion severity increased over time with 90 and 123 counties being classified into the highest severity class for the first and second measurement, respectively. Further, the invasibility of major forest-type groups by severity class was examined using the product of the county-level mean presence probability and mean cover percentage of Chinese tallow as a proxy of invasibility. Longleaf/slash pine ( Pinus palustris/P. elliottii ) forests were highly resilient to the Chinese tallow invasion. In contrast, elm/ash/cottonwood ( Ulmus spp./Fraxinus spp./Populus deltoides ) and oak/gum/cypress ( Quercus spp./Nyssa spp./Taxodium spp. ) forest-type groups were vulnerable to invasion.